2018
DOI: 10.1080/09638288.2017.1423520
|View full text |Cite
|
Sign up to set email alerts
|

Can the physical environment itself influence neurological patient activity?

Abstract: Overall, patient social and physical activity was low, with little to no use of communal spaces. However we found more physical activity in patient rooms in the Ward B environment. Given the potential for patient activity to drive brain reorganization and repair, the physical environment should be considered an active factor in neurological rehabilitation and recovery. Implications for Rehabilitation Clinicians should include consideration of the impact of physical environment on physical and social activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…[35] As physical activity may enhance recovery after neurological injury, the physical environment of patients who suffer debilitating neurologic injury has been considered following such injuries, namely stroke. [36] Stroke requires rapid treatment to limit the extent and severity of brain damage; previous studies have found that every minute of delay may contribute to the destruction of 1.9 million cerebral neurons. [37] tPA is an effective treatment for acute ischemic stroke within 4.5 h of the initial onset of symptoms with greater amounts of time decreasing efficacy which further highlights the significance of time in treatment.…”
Section: Methodsmentioning
confidence: 99%
“…[35] As physical activity may enhance recovery after neurological injury, the physical environment of patients who suffer debilitating neurologic injury has been considered following such injuries, namely stroke. [36] Stroke requires rapid treatment to limit the extent and severity of brain damage; previous studies have found that every minute of delay may contribute to the destruction of 1.9 million cerebral neurons. [37] tPA is an effective treatment for acute ischemic stroke within 4.5 h of the initial onset of symptoms with greater amounts of time decreasing efficacy which further highlights the significance of time in treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies showed an association between the well-being of patients and staff at healthcare facilities and the design of the physical environment [12][13][14][15]. In stroke units, the physical environment has been described as essential for patient activities and care [16][17][18]. Changes in the physical environment have been found to influence patient activity and social interactions [16].…”
Section: Introductionmentioning
confidence: 99%
“…In stroke units, the physical environment has been described as essential for patient activities and care [16][17][18]. Changes in the physical environment have been found to influence patient activity and social interactions [16]. In a recent study, patients were found to have higher levels of activity in a stroke unit that had a combination of single and multibed room designs compared to a stroke unit with only a singleroom design [18].…”
Section: Introductionmentioning
confidence: 99%
“…front of the elevators, to encourage social interaction and time away from the bedside. Physical build design of the ward can impact on patient activity (Blennerhassett et al, 2018;Shannon et al, 2018). For example, a study that tracked stroke patients in a stroke unit pre and post reconstruction of the environment highlighted how location of the communal space and bed lay out (single vs. multi-bedrooms) influenced activity levels of stroke patients (Anaker et al, 2017).…”
Section: Effect Of Enrichment On Amount Of Staff Assistancementioning
confidence: 99%
“…Findings indicated that in the new build environment patients spent more time in their rooms, were less active, and had fewer interactions with staff and family than patients in the original unit (Anaker et al, 2017). Until now, only a few studies have investigated how patient activities relate to lay out of the physical design of the unit and have highlighted that physical design may impact on patients' activity levels (Anaker et al, 2017;Blennerhassett et al, 2018;Shannon et al, 2018). While there is a push towards single bedrooms for reasons such as infection control, the possible impact on stroke recovery, activity levels and interaction with others needs to be seriously considered as well (Maben et al, 2016;Pennington & Isles, 2013).…”
Section: Impact Of the Physical Build Design Of The Unitmentioning
confidence: 99%